Feasibility Study of LTE Network Implementation on Working Frequency 700 MHz, 2100 MHz, and 2300 MHz in Indonesia - Feralia Fitri; Rendy Munadi; Nachwan Mufti Adriansyah (eProceedings of Engineering, 2021)
The increasing density of data traffic leads to an increase in the demand for telecommunication services. Therefore, in this study, the LTE network expansion was carried out using a choice of frequencies of 700 MHz, 2100 MHz, and 2300 MHz. The analysis was carried out from the technical, economic, and sensitivity aspects. Sensitivity analysis was used to determine the minimum ARPU for each candidate frequency. This research was conducted using a case study of the city of Yogyakarta. Based on the simulation results, the average RSRP values for the three candidate frequencies are in the very good range. The SINR values for the three candidate frequencies are in the normal category and the throughput values are in the very good category. The techno-economic calculations of IRR, NPV and payback period for the frequencies of 2100 MHz and 2300 are included in a feasible business, while at a frequency of 700 MHz it is not feasible to do so. The results of the sensitivity analysis show that the frequency of 2300 MHz is a feasible frequency to be implemented for LTE networks with the minimum ARPU and the minimum number of users. This research can be used for the operator as a consideration for the implementation of other frequencies on LTE networks. Keywords— capacity planning, coverage planning, LTE, techno economy, sensitivity analysis